Strategi dan Prospek Pengembangan Jambu Mete (Anacardium Occidentale. L) Kabupaten Jember - Bagus Putu Yudhia Kurniawan (Universitas Airlangga, 2016)
The increasing growth of world cashew consumption is an opportunity for Indonesia and East Java province to increase cashew production. Cashew production on a national scale reached 95,000 tons per year. East Java province contributed about 11% of the national cashew production. Jember is famous as a center for cashew producer in the Eastern region of East Java province and has great potential in the development of agribusiness/agroindustry cashew nuts. However, they found some of problems that hamper the success of cashew farming. The purpose of this study is to formulate a strategy and analyze the development prospects for of cashew Jember Regency. The analysis technique used were Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Relative Competitive Position matrix, Internal and External (IE) matrix, and SWOT matrix. The results showed that internal factors are a major force in cashiew farming was cultivation techniques, while being the weakness was the production and marketing. External factors were the largest opportunity in the farming of cashew was the suitability of land and government policies, while the greatest threat is climate risks and uncertainties. The strategy recommended in the development of cashew Jember Regency is a growth-oriented strategy through horizontal integration (concentration through horizontal integration) with strategic priorities: (1) improving farming techniques with input suitable productive land, quality seeds and adequate capital, so that the product cashew produced can be more qualified and have a more competitive price in the market; and (2) more consistently maintaining the quality of the product, so that the consumer confidence is also increasing.